Risk perception and coping strategies in population exposed and not exposed to flooding risk - Navarro, Oscar; Chaves, Liliana; Pineres Sus, Juan David; Noreña Betancur, Maria Isabel (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study seeks to link risk perception with personal involvement and coping strategies to face the flood threat, comparing people exposed with people not exposed to this risk. We found that people exposed to flooding have a better knowledge of risk, more fear of being affected and develop more coping strategies than unexposed people. Within the risk exposed people’s category, we can find a difference between those who have been actually affected by floods and those who are living in a risky place but not have been affected yet, in the way that first of them present a higher level of risk perception and personal involvement. Finally, the mediating role of the personal involvement variable between perception of risk and active coping strategy has been confirmed